Drug/Lead Compound Hydroxymethylation as a Simple Approach to Enhance Pharmacodynamic and Pharmacokinetic Properties - Santos, Soraya S.; Gonzaga, Rodrigo V.; Scarim, Cauê B.; Giarolla, Jeanine; Primi, Marina C.; Chin, Chung M.; Ferreira, Elizabeth I. (Frontiers in Chemistry, 2022)
Hydroxymethylation is a simple chemical reaction, in which the introduction of the hydroxymethyl group can lead to physical-chemical properties changes and bring several therapeutic advantages, contributing to improving the biological activity of drugs. There are many examples in the literature of the pharmaceutical, pharmacokinetic, pharmacodynamic benefits, which the hydroxymethyl group can confer to drugs, prodrugs, drug metabolites, and other compounds available on therapeutics. It is worth noting that this group can enhance the drug interaction with the active site, it can be employed as an intermediary in synthesizing other therapeutic agents. In addition, the hydroxymethyl derivative can result in more active compounds than the parent drug as well as can increase the water solubility of poorly soluble drugs. Considering that, this review aimed to discuss the different applications of hydroxymethyl derived from biological agents and its influence on pharmacological effects of drugs, prodrugs, active metabolites, compounds of natural origin. Finally, we report a well-succeeded compound obtained by our research group for neglected diseases treatment designed from hydroxymethylation of the parent drug.